1995
DOI: 10.1161/01.atv.15.10.1599
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Lecithin-Cholesterol Acyltransferase and Modification of HDL Apolipoproteins by Aldehydes

Abstract: Experimental evidence suggests that aldehydes generated as a consequence of lipid peroxidation may be involved in the pathogenesis of atherosclerosis. It is well documented that aldehydes modify LDL: however, less is known concerning the effects of aldehydes on other plasma and interstitial fluid components. In the present study, we investigated the effects of five physiologically relevant aldehydes (acetaldehyde, acrolein, hexanal, 4-hydroxynonenal [HNE], and malondialdehyde [MDA]) on two key constituents of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
1

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 44 publications
8
53
1
Order By: Relevance
“…A pattern of cross-linking of HDL apoproteins like that induced by tyrosyl radical (including apparent apoAI-apoAII heterodimers) is indicated in previous reports using manganese, copper, cigarette smoke, or aldehydes to oxidize HDL particles (51)(52)(53)(54). We have found that incubation of HDL with the crosslinking agent tetranitromethane induces a similar pattern.…”
Section: Discussionsupporting
confidence: 75%
“…A pattern of cross-linking of HDL apoproteins like that induced by tyrosyl radical (including apparent apoAI-apoAII heterodimers) is indicated in previous reports using manganese, copper, cigarette smoke, or aldehydes to oxidize HDL particles (51)(52)(53)(54). We have found that incubation of HDL with the crosslinking agent tetranitromethane induces a similar pattern.…”
Section: Discussionsupporting
confidence: 75%
“…Aldehydes such as 4-hydroxynonenal and malondialdehyde generated during LDL oxidation can cause apo A-I cross-linking in HDL. 39 Two possible mechanisms for the decreased protection exhibited by HDL 2 from diabetic subjects include the following: (1) The decreased free cholesterol concentration seen in diabetic HDL 2 may alter its surface fluidity, perhaps thereby facilitating the lipid peroxides generated during LDL oxidation to "seed" the HDL 2 . Once seeded with lipid peroxides, the TG-enriched HDL 2 from diabetic subjects may be more susceptible to oxidation and become less protective.…”
Section: Gowri Et Al Decreased Protective Function Of Hdl In Niddm 2231mentioning
confidence: 99%
“…A variety of reactive aldehydes modify HDL and appear to cross-link its proteins in vitro (30). Modification is associated with loss of the ability of HDL to activate lecithin-cholesterol acyltransferase (30), a key enzyme in reverse cholesterol transport.…”
mentioning
confidence: 99%